Resistance and acceptance of posyandu cadres to the digitization of stunting recording: qualitative analysis of empowerment-based technology acceptance model (case study in Gegerkalong village, Bandung city) - Anne Rahaju; Dede Rohidin (Institute of Computer Science (IOCS), 2026)
The transformation of maternal and child health data recording from manual methods to digital systems poses significant socio-technical challenges at the grassroots level. This study aims to analyze the dynamics of resistance and acceptance of Posyandu cadres in Gegerkalong Village, Sukasari District, Bandung City towards stunting recording technology, by integrating the Technology Acceptance Model (TAM) and the andragogy approach. Using a qualitative approach with a case study design, data collection was carried out through in-depth interviews, participatory observations, and Focus Group Discussions (FGD) involving 12 participants (senior cadres, young cadres, and health workers). The results of the study show that technological resistance is mainly triggered by the mismatch of interface design (User Interface) with the cognitive and visual capacity of adult learners, which leads to cognitive overload and low Perceived Ease of Use. On the other hand, revenue is driven by the perception of Perceived Usefulness when digital reporting is considered to be able to increase efficiency and raise the social status of cadres in society. This research underlines the importance of integrating the concept of lifelong education and peer tutoring methods in cadre mentoring. It is recommended that the design of future health information systems involve end users (cadres) in the development phase to realize inclusive technology